The politics of the prison and the prisoner: zoon politikon - Easton, Susan M. (Routledge, 2018)
The prisoner as a zoon politikon -- Political protest in prison -- The quest for citizenship in prison -- Losing citizenship in prison -- Discovering politics in prison -- The treatment of political prisoners -- Prisoners as a political problem -- Bibliography -- Index